Assessing readiness for performance audit - Bautista, Victoria A. (Philippine Journal of Public Administration, 1983)
A new thrust in government auditing is performance audit. Presidential Decree No. 1445 directs the Commission on Audit to conduct performance audit covering the 3Es, i.e., efficiency, economy, and effectiveness. In this regard, an assessment of the preparedness, in terms of technical psychological and actual involvement/participation in performance audits of COA personnel is made. External and internal organizational factors which impede the conduct of audit are examined Some of the general findings include the following: majority of the respondents have low technical preparedness and low actual participation. Very few of the respondents have participated in training programs necessary for performance audit. A small number of respondents have actually experienced performance auditing through their participation in the conduct of 3Es audit. Respondents with and without experience in performance audit expressed similar problems: (1) lack of technical preparation to pursue performance audit (2) lack of performance indicators standards, and (3) lack of technical preparation on the part of the team members. The recommendations are addressed at strengthening the internal capability of COA to conduct performance audi harnessing inter-agency support for performance audit, and rationalizing the organizational machinery responsible for the administration of programs and projects.